Local development and agricultural dynamics in the Guisa municipality (Review) (REDEL. Revista Granmense de Desarrollo Local, 2019)
Local development requires alternative solutions and ways to achieve them conceived by the companies themselves. In this process the municipalities are placed with an important role, as a space for the construction of their own development. The objective of the work is to present elements that intervene in the management of local development, particularly in the agricultural dynamics of Guisa municipality, Granma province. The analysis carried out showed that the adequate participatory design of the Integral Development Program (PDI) is needed. The practice of Local Development in Guisa shows shortcomings related to low levels of culture of participation in local actors, especially decision-makers and the agricultural sector. It is necessary to design and implement differentiated learning strategies for the municipal government and the Agriculture System of the municipality to enable the understanding of innovation processes for local development and provide tools on how to do them. Key words: local development; integral development program; innovation; sustainability; agriculture.
Keywords: local development; integral development program; innovation; sustainability; agriculture.